Population analysis of beef herds in southern Ghana - Ahunu, B K; Amponsah, R Osei; Osei, J B; Aboagye, G S (The Indian Journal of Animal Sciences, 2012)
Lifetime records involving 22 full cohorts of cows born at the Aveyime commercial cattle ranch and 26 full cohorts of cows born at the University of Ghana Beef Cattle Research Station at Kpong were analysed for descriptive life table statistics. The 2 herds were raised under similar climatic but slightly different managerial and culling practices. Nine life table statistics were studied, namely, age-specific survivorship -(Lx); age-specific survival rate (Px) and age-specific mortality rates (Qx); expected herd life (Ex); average number of daughters per cow at a particular age x (Mx); reproductive value (Vx); net reproductive rate (Ro); generation interval (T) and instantaneous rate of population increase (r). In both herds Lx and Px values decreased with increasing age. Expected herd life for yearlings were 5.26 and 5.28 years for Aveyime and Kpong respectively. The average number of daughters per cow (Mx) was 0.45 for A veyime and 0.54 for Kpong with net reproductive rate (Ro) being 1.80 apd 1.86, respectively, for Aveyime and Kpong indicating that on the average cows in these herds produced more than one replacement heifer (i.e. replaced themselves) before being disposed of. Estimates of the generation interval (T) were respectively 5.72 and 6.93 at Aveyime and Kpong whilst the instantaneous rate of population increase (r) was positive and greater than zero in both herds indicating increasing herd numbers on the 2 ranches.